Preliminary characterization of arracacha Arracacia xanthorrhiza Bancroft crop in the department of Boyaca - Muñoz, Astrid Lorena; Alvarado G., Alvaro; Almanza M., Pedro José (Revista de Ciencias Agrícolas, 2015)
In the department of Boyaca, and in Colombia in general, studies on the genetic diversity of arracacha are scarce. A preliminary identification of the existing genetic material in the producing municipalities of the department of Boyaca was conducted. Visits to production farms were made in order to document the knowledge regarding the species and other aspects of the production system. A qualitativedescriptive methodology was used, based on non-metric criteria for data collection, depending on the research characteristics and the researcher’s criteria. Plant material samples were collected and the following traits were recorded: leaf color, stem color, color and presence of the root ring. Three main leaf colors were determined: green, purple-green, and purple. Regarding the stem, green and reddish-purple were observed. The root showed a white or yellow color, with white or purple colored oil vessels. The existence of six genetic materials was determined, which were named Huevo, Paliverde, Palirrusia, Palinegra, Sata, and Satamorada.